2016
DOI: 10.1055/s-0036-1580713
|View full text |Cite
|
Sign up to set email alerts
|

High Risk HPV E6/E7 Oncoprotein Expression in Women with High Grade Squamous Intraepithelial Lesion

Abstract: E6/E7 mRNA expression was higher in women with HSIL and CIN grade 2 or higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, the antigen-processing was significantly impaired, which was measured by proteolytic cleavage of DQ-OVA and the activation of T cells by APCs [12]. Furthermore, there was a study that found that E7 mRNA expression was higher in women with high grade squamous intraepithelial lesion (HSIL) and cervical intraepithelial neoplasia (CIN) grade 2 or higher [13]. HPV E7 may also induce the upregulation of RRM2, which then promotes cervical carcinogenesis via ROS-ERK1/2-HIF-1α-VEGF-induced angiogenesis [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the antigen-processing was significantly impaired, which was measured by proteolytic cleavage of DQ-OVA and the activation of T cells by APCs [12]. Furthermore, there was a study that found that E7 mRNA expression was higher in women with high grade squamous intraepithelial lesion (HSIL) and cervical intraepithelial neoplasia (CIN) grade 2 or higher [13]. HPV E7 may also induce the upregulation of RRM2, which then promotes cervical carcinogenesis via ROS-ERK1/2-HIF-1α-VEGF-induced angiogenesis [14].…”
Section: Discussionmentioning
confidence: 99%
“… ∗ Excluding CIN2 from analysis. CIN: cervical intraepithelial neoplasia; CI: Confidence interval; DOR: diagnostic odds ratio; AUC: area under the curve; TP: true positive; FP: false positive; FN: false negative; TN: true negative.Included studies CIN1- vs. CIN2+: Aptima [835]; NucliSens EasyQ HPV [3646]; OncoTect [41, 4751]; PreTect HPV Proofer [14, 23, 25, 31, 5261]; Quantivirus [45, 6265]. CIN1- vs. CIN3+: Aptima [815, 18–22, 24, 2631, 3335]; NucliSens EasyQ HPV [36, 37, 41, 46]; OncoTect [41, 47–50]; PreTect HPV Proofer [14, 31, 5961]; Quantivirus [62–64].…”
Section: Figurementioning
confidence: 99%
“…Included studies CIN1- vs. CIN2+: Aptima [835]; NucliSens EasyQ HPV [3646]; OncoTect [41, 4751]; PreTect HPV Proofer [14, 23, 25, 31, 5261]; Quantivirus [45, 6265]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that 55.6% of women with CIN2,3 had E6/E7 mRNA. In studies by Castle et al (22) and Valença et al (23), E6/E7 mRNA was detected in 84% and 70% of cases with a high-grade squamous intraepithelial lesion (HSIL), respectively. Negative results in CIN2,3 cases can be because of the low level or lack of transcriptional activity.…”
Section: Methodsmentioning
confidence: 97%